APPLICATION OF AKAD IJARAH ISLAMIC LAW IN THE AL-QUR'AN - Jamarudin, Ade; Pudin, Ofa Ch (Islamika : Jurnal Agama, Pendidikan dan Sosial Budaya, 2020)
Ijarah is a contract on the transfer of goods or services with rewards instead. Ijarah based transactions with the displacement benefit (rights to), not transfer of ownership (property rights), there ijara financing translates as buying and selling services (wages hired), that take advantage of human power, there is also a translate lease, which take advantage of goods. Application ijarah growing financial institutions in the current Shari'ah is happening on the leasing company (financial institution based on Islamic teachings, as well as Islamic banking is one of the products in Islamic finance. Application ijarah emerging financial institutions shari'ah 'ah at the moment that is happening on the leasing company (financial institution based on Islamic teachings, as well as Islamic banking is one of the Islamic financing products). This research is a library research (library research) and field research (field research), and is descriptive, analytic and comparative. Data sources used in this study are sourced from primary and secondary data. Ijarah transactions are based on the transfer of benefits (use rights), not the transfer of ownership (ownership rights), some translate ijarah financing as the sale and purchase of services (wage wages), i.e., taking the benefits of human labor